1990
DOI: 10.1177/00220345900690s117
|View full text |Cite
|
Sign up to set email alerts
|

Tooth-bound Fluoride and Dental Caries

Abstract: The cariostatic effects of tooth-bound fluoride reported in the recent literature are reviewed. Several treatment procedures which can increase the tooth-bound fluoride content are described. Based on this information, it is suggested that effectiveness of currently used topical fluoride treatments may be significantly increased by (1) including in the regimen a dicalcium-phosphate-dihydrate-forming treatment so that a portion of the labile fluoride is re-incorporated as tooth-bound fluoride, and (2) employing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 41 publications
(24 reference statements)
0
22
0
Order By: Relevance
“…On the other hand, this result is consistent with the current concept that successful resistance to carious challenges requires a continuing supply of inhibition products, rather than a static, limited, stored supply. 8 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this result is consistent with the current concept that successful resistance to carious challenges requires a continuing supply of inhibition products, rather than a static, limited, stored supply. 8 …”
Section: Discussionmentioning
confidence: 99%
“…This study, which found no difference in lactate production following a fluoride dentifrice, employed pooled samples, which have been identified as a confounding factor in such measurements [Rankine et al, 1985;Vogel et al, 1990;Ekstrand et al, 1990]. A second mechanism by which fluoride may exert a cariostatic effect during demineralization involves a reduction in calcium phosphate solubility [Chow, 1990] and hence a reduction in the rate of dissolution of enamel mineral. Especially noteworthy in regard to this mechanism are studies suggesting that the observed very large effect of solution fluoride on enamel dissolution [Margolis and Moreno, 1990] may be attributed to the formation of fluorapatite (FAp) or partially fluoridated hydroxyapatite (OHAp) at the active sites of mineral destruction [Arends and Christoffersen, 1990].…”
mentioning
confidence: 82%
“…Different solid solutions of fluorhydroxyapatite can form, depending on the fluoride concentration in the solution (Driessens, 1982;LeGeros, 1991). It is an important consideration that when a tooth surface is equilibrated with oral fluids containing fluoride, the most stable phase of fluorhydroxyapatite is produced, which effectively maximizes the stability of the tooth mineral in the oral environment (Chow, 1990;Shellis and Duckworth, 1994). Topical treatment of tooth enamel with acidic fluoride-containing solutions or fluoride-releasing compounds leads to formation of CaF2 or phosphate-containing CaF2-like materials, which are viewed as a potential reservoir source for solution ionic fluoride (Nelson et al, 1983).…”
Section: Fluoride In Apatite Structurementioning
confidence: 99%